Characterization of carotenoids content and composition of saffron from different localities - Othman, Rashidi; Mohd Hatta, Farah Ayuni; Mohd Hassan, Norazian; Kammona, Suhair (SET PUBLISHER, 2020)
The most essential carotenoids for humans are found in plants that are normally yellow, orange, and red coloured pigments. They are typically and mostly lipophilic in nature, but some unique plant species may yield watersoluble carotenoids. Saffron or Crocus sativus contains hydrophilic carotenoids named crocin. Thus, this paper will describe the extraction and characterization of hydrophilic and lipophilic carotenoids (colour properties) obtained from saffrons of different geographical origins. They are specifically the Iranian, Turkish, and Kashmiri saffron respectively. Maceration techniques have been employed to extract the targeted compounds, whereas the characterization of the compounds has been analysed using HPLC. The extraction and characterization of carotenoids in saffron from different geographical origins found that the amount of crocin content was substantially higher in Iranian saffron, which was 11414.67 ± 516.34 μg/g DW followed by Turkish and Kashmiri saffron. Lipohilic carotenoids (i.e. crocetin, β-carotene, and zeaxanthin) were detectable in Iranian and Turkish saffron but absent in Kashmiri saffron. Similarly, the highest amount of crocetin content was found in Iranian saffron at 1054.73 ± 50.31 μg/g DW, while the highest amount of β-carotene and zeaxanthin was found in Turkish saffron at 512.92 ± 79.98 μg/g DW and 252.04 ± 60.34 μg/g DW, respectively. There was a marked difference in carotenoid composition sourced from different localities. Various environmental factors like climatic conditions, agricultural practices, stigma separation, and storing and drying processes may play an important role to explain such difference